(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
درست المؤشرات الحيوية والحياتية للأكاروس الأحمر ذي البقعتين Tetranychus urticae (Koch) عند حرارة 1±25 Cº ، ورطوبة 5±65%، و 8:16 ساعة إضاءة/ظلام، وعلى أوراق صنفين من التفاح ( غولدن, ستاركنغ ديليشز). كان معدل الزيادة الفعلية rm لإناث T.urticae على أوراق الصنف ستاركنغ أعلى مقارنة مع الصنف غولدن (0.30 و 0.27 أنثى/أنثى/يوماً على التوالي), في حين كانت مدة زمن الجيل (T)، والمدة اللازمة لتضاعف أعداد مجتمع الأكاروس (DT) على الصنف ستاركنغ أقل منه على الصنف غولدن (13.77, 2.3 و 14.54, 2.55 يوماً على التوالي)، استغرق التطور من البيضة إلى الأنثى البالغة على الصنف غولدن مدة زمنية أطول بالمقارنة مع الصنف ستاركنغ, (13.32 ±1.15 و 12.22±1.13 يوم على التوالي). كان معدل الخصوبة الكلية، و طول عمر البالغة على الصنف غولدن أقل منه على الصنف ستاركنغ (83.11±8.91 ، و 101.62±15.48 بيضة/أنثى على التوالي)، و (15.33 ±1.35 و 17.14±1.07 يوماً على التوالي). يمكن أن تعزى هذه الاختلافات على صنفي التفاح إلى المحتوى الكيميائي، و نوعية الغذاء، و طبيعة النسيج الورقي للعائل النباتي، و هذه المواصفات يمكن أن تؤثر في معدل وضع البيض و التطور، ومن ثَمّ كان الصنف ستاركنغ أكثر ملائمة لتطور الأكاروس الأحمر ذي البقعتين و تكاثره، مقارنة مع الصنف غولدن. Biological characteristics and life table parameters of the two-spotted spider mite Tetranychus urticae (Koch) were studied when fed on leaves of two apple cultivars (i.e. Golden and Starking dilishz) under laboratory conditions 25±1 Cº, relative humidity 65±5% and 16L:8D. The intrinsic rate of increase (rm) by females of T.urticae was higher on leaves of Starking dilishz apple cultivar than on leaves of Golden dilishz apple cultivar (0.30, 0.27 female/female/day) respectively, while the generation time (T) and the time required for doubling the number of community mite (DT) were lower on leaves of Starking dilishz apple cultivars than on leaves of Golden dilishz apple cultivars (13.77, 2.3 days and 14.54, 2.55 days) respectively. The duration of the stages of growth from egg to adult female on leaves of Golden dilishz apple cultivar was longer than on Starking dilishz apple cultivars, where was (13.32 ± 1.15 and 12.22 ± 1.13), respectively, The Total fecundity on Golden dilishz apple cultivar was lower than on Starking dilishz cultivar (83.11 ± 8.91, 101.62 ± 15.48 eggs/female) respectively, The adult longevity on Golden dilishz leaves was lower than on Starking dilishz cultivar (15.33 ± 1.35, 17.14 ± 1.07 days) respectively, These differences on the apple varieties may be due to the chemical content and quality of the food and nature of the host tissue plant and the specifications can affect the rate of oviposition and development. and thus the Starking dilishz apple cultivars was more suitable for the development and reproduction of T. urticae compared with the Golden dilishz apple cultivar.